Thermodynamic analysis of processes creating the defects in cadmium telluride crystals under conditions of high-temperature annealing - Prokopiv, V.V.; Fochuk, P.M.; Gorichok, I.V.; Vergak, E.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2009)
The defective structure of specifically undoped cadmium telluride crystals was
researched using the theory of thermodynamic potentials. The calculated concentration of
point defects and free charge carriers in the CdTe crystals, depending on technological
factors of two-temperature annealing (annealing temperature T and partial pressure of
cadmium PCd vapor). The dominant types of defects that determine the basic properties
of the material n- and p-type conduction were determined.